Dr.J. Jayalalitha Excellence Leadership Quality: Shaping Regional and National Politics in India—A Comprehensive Study. - E. Kaviyarasu; Shabir Ahmad Lone; S. Navaneethakrishnan (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Dr.J.Jayalaitha, a prominent political leader in Tamil Nadu, is widely recognized for her transformative leadership and the significant impact of her welfare schemes, which aimed to improve the lives of her constituents. Notable initiatives, such as Amma Unavagam (low-cost canteens), the establishment of special police stations for women, and Amma Pharmacies offering affordable medicines, reflect her unwavering commitment to social welfare. This historical and descriptive article study examines the historic events and political success of Dr.J.Jayalaitha, focusing on the social welfare schemes she introduced. The paper assesses her leadership qualities through the lens of established leadership theories, demonstrating that her leadership was not only effective but transformative. The analysis also explores why the people of Tamil Nadu affectionately referred to Dr.J.Jayalaitha a as "Amma," a term meaning "mother," signifying her deep connection to the people and her role as a great leader.